Identification of soluble proteins present in giant squid (Dosidicus gigas) meal for human consumption - Juan Rodolfo Omote-Sibina; David Julián Roldán-Acero (Agronomía Mesoamericana, 2023)
Introduction. The giant squid (Dosidicus gigas) is a species of great abundance and considered as potential resource to meet the demand for protein in Peru. Giant squid meal represents an alternative to traditional proteins which can be used in food fortification. Objective. To optimize the extraction process and identification of soluble protein from giant squid meal (GSM). Materials and methods. This study was conducted at the Universidad Nacional Agraria La Molina, Lima, Peru, between 2018 and 2019. To obtain the highest yield of soluble protein (Ŷ) extracted, an alkaline extraction method using NaOH followed by acid precipitation at pH 4.5 was applied. Surface response methodology was used to determine the optimal parameters for protein extraction such as temperature, concentration of NaCl, time, and the ratio GSM: solvent. A 1D and 2D electrophoresis study was carried out to find the distribution of molecular weights and to identify the main proteins of GSM. Results. Values for optimal response were the concentration of NaCl 0 M, an extraction time of 35 min, the ratio GSM: solvent of 1:31.72, and a temperature at 71.9 ºC. The molecular weights of the proteins detected were in the range of 6.5 and 38.37 kDa, which would correspond to tropomyosins, troponins, and myosin light chain residues. Conclusions. This study allowed to optimize the extraction parameters and to identify soluble proteins corresponding to the sarcoplasmic fraction of the giant squid meal (GSM), which could be used in the food industry.